EDUKASI PEMERIKSAAN PAYUDARA SENDIRI PADA WANITA USIA SUBUR SEBAGAI UPAYA PENCEGAHAN DINI KANKER PAYUDARA - Puspita, Irma Yudith Ayu; Mulyati, Susi; Mahanani, Dian; Budianto, Eko Teguh; Apriliani, Fauziah; Zulfa, Habibah; Wahidatunnisa, Isda Rahma; Hafizah, Iva; Putri, Kharisma Fadila; Fitri, Raissa Ananda (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Breast cancer, a malignant tumor, remains the leading cause of cancer-related deaths among women globally. This is supported by data from the World Health Organization (WHO), which reported nearly 1.7 million new cases in 2012, accounting for approximately 12% of all cancer diagnoses and 25% of cancers in women. By 2010, WHO estimated that breast cancer incidence had reached 11 million cases, and global cancer-related deaths were projected to rise to 27 million by 2030. Early detection of breast cancer is achievable through self-breast examination (SADARI). Without regular self-examinations, breast cancer is often diagnosed at an advanced stage, significantly increasing mortality risk. Early detection can reduce mortality rates by 25–30%. Monthly self-examinations are strongly recommended, and individuals should seek immediate medical consultation if a lump is detected. This practice is critical for public health, including adolescents, as 86% of breast lumps are first identified through self-examination. Increased awareness of SADARI positively influences women’s attitudes and behaviors, emphasizing its role in reducing breast cancer risk. Notably, women in early adulthood are more likely to adopt regular self-examinations to monitor breast health proactively. A community service initiative was conducted to educate 30 participants about SADARI. Knowledge levels were evaluated using pre-test and post-test questionnaires. The results showed a significant improvement in understanding, with 23 respondents (76.66%) achieving high post-test scores, demonstrating the effectiveness of the educational outreach.